Symbioza nazw, czyli o intertekstualności onimicznej - Rutkiewicz-Hanczewska, Małgorzata (Slavia Occidentalis, 2012)
The present article is devoted to a textological analysis of the so-called intertextual proper names, i.e. units that relate to the structure of names that have been constructed earlier. The article attempts to characterize the so-called proprial (onymic) texts with the relations taking place between the hypotext (cf. “source name”) and the hypertext and/or hypertexts (cf. target name) taken into consideration. Considering the way particular texts are derived via a transition of some kind, a number of types has been distinguished: transtextualization, intertextualization, transformation, iconization and imitation. Transtextualisation involves names transferred from one onymic plane to another without any formal change (cf. Polish Pożegnanie z Afryką (Out of Africa) – the title of a film > Pożegnanie z Afryką – the name of a branch of shops in Poland). Transformations are names that have originated as a result of different linguistic transformations of the source text, i.e. the hypotext (cf. Skierniewice – a place name of a town > the Skierniewka – the name of a river). Imitations correspond to names formed in artificial onymic conditions, through analogy to structures already existing in the propial tradition (e.g. Biedaczkowo [Penuryville] – a text in the function of a place name, Bezczelnicki – a joke name to be found in literature). Intextualisations are, in turn, names whose structure contains hypotexts resulting from indirect influence or more or less precise application of their structure (cf. Słoń Torbalski – the name of a fancy leather goods manufacturer from the classic verse by J. Tuwim about its eponymous protagonist, the forgetful elephant, Tomasz Trąbalski). Finally, iconizations are created as a result of a transformation of the structure of pastiche-type hypotext or parody or burlesque (cf. Rozmowy w tłoku < Rozmowy w toku). The article also discusses differences between the so-called classic(archetypal) and prioprial text, as well as the functions of intertextual appellative texts, that involves updating of name-resources of a given system, among others.